Long-term exposure of Mytilus galloprovincialis to diclofenac, Ibuprofen and Ketoprofen: Insights into bioavailability, biomarkers and transcriptomic changes. (May 2018) - Mezzelani, M.; Gorbi, S.; Fattorini, D.; d'Errico, G.; Consolandi, G.; Milan, M.; Bargelloni, L.; Regoli, F.
Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) represent a growing concern for marine ecosystems due to their ubiquitous occurrence and documented adverse effects on non-target organisms. Despite the remarkable efforts to elucidate bioaccumulation and ecotoxicological potential under short-term conditions, limited and fragmentary information is available for chronic exposures. In this study bioavailability, molecular and cellular effects of diclofenac (DIC), ibuprofen (IBU) and ketoprofen (KET) were investigated in mussels Mytilus galloprovincialis exposed to the realistic environmental concentration of 2.5 μg/L for up to 60 days. Results indicated a significant accumulation of DIC and IBU but without a clear time-dependent trend; on the other hand, KET concentrations were always below the detection limit. Analyses of a large panel of molecular, biochemical and cellular biomarkers highlighted that all investigated NSAIDs caused alterations of immunological parameters, genotoxic effects, modulation of lipid metabolism and changes in cellular turn-over. This study provided the evidence of long-term ecotoxicological potential of NSAIDs, further unraveling the possible hazard for wild marine organisms. Highlights: Long-term ecotoxicological effects of NSAIDs were investigated in mussels. Significant accumulation occurred for diclofenac, ibuprofen, not for ketoprofen. All NSAIDs determined transcriptional and cellular effects in mussels. Immune responses were the main targets of long-term exposure to NSAIDs. Transcriptional changes supported variations of cellular biomarkers.